Membranes for industrial wastewater recovery and re-use - Judd, Simon; Jefferson, Bruce (Kidlington, Oxford, UK ; New York, NY, USA : Elsevier Science, 2003)
There is increasing political and environmental pressure on industry to clean up the water which it uses in many processes, and to re-use this water where possible. This cleaning is done using specially-developed industrial membranes and this book covers the types and design of membranes, how they work and in which industries they are used. Special attention is paid to the textile, food/ beverage, pharmaceutical, oil and pulp and paper industries where such membranes are in regular use.
Membrane technology -- Industrial waters -- Commercial systems -- Case studies.
Includes bibliographical references and index.
Keywords: Sewage -- Purification; Factory and trade waste -- Purification; Membranes (Technology).; Water reuse; Electronic books